Implementasi Pembelajaran Berbasis Proyek pada Mata Kuliah Kewirausahaan Mahasiswa Pendidikan Biologi - Titin, Titin; Komaria, Siti; Yolasari, Putri (Perkumpulan Pendidik Kewirausahaan Indonesia (Perwira Indonesia), 2024)
This research is qualitative descriptive research. This type of research was chosen with the aim of describing the implementation of Project-Based Learning models (PJBL) in entrepreneurship courses at the Faculty of Teacher Training and Education, Tanjungpura University. The research's population is students of the biology education program and the research's sample is 50 students of the biology education. The research methods used non-conservative observation, documentation, and the research instrument is a response questionaire. The respons questionaire used to measure students' motivation, understanding, and experience during the learning process using the PJBL model. The results of the study showed that the motivational aspect gained 76.4% with strong interpretation; the understanding of 85.1% interpretation very strong, and the experience of 79.5% interpretation was strong. In line with the results, it can be concluded that the implementation of Project-Based Learning models or can improve students' learning motivation, understanding, and experience in entrepreneurship courses in biology education